The setting of horror in six short stories by H. P. Lovecraft - Vuorinen, Laura (My University, 2022)
In this thesis I examine how the setting of horror is described and, thus, constructed in stories of weird horror fiction by H. P. Lovecraft. Lovecraft (1890–1937) is known for his attention to setting and use of adjectives. My corpus consists of six short stories from the first half of the 1920s. My focus is on the use of the chronotope and vocabulary, mostly adjectives, in the text. In addition, I am interested in the role of nature in the setting. Using Bakhtin’s chronotope I study the way time and place together create the setting and affect the story. The actions of the characters are both limited by the location and indicative of the progress of the story by what they do there. I examine the presence of nature through ecocriticism. In this I rely mostly on Tabas, Kröger, and Corstorphine as I discuss nature in horror setting. The most relevant topics are how natural elements are described and how the power of nature is presented. The three main results of this study are the following: First, many of the places form a threshold, either literally between two places or figuratively between two purposes. Second, nature is much more powerful and grand than humans or anything they make. Third, Lovecraft’s use of adjectives is ample and fitting; it creates much of the weird and horrible in his stories. It would be very interesting to expand the research to cover Lovecraft’s entire oeuvre.
Keywords: setting, H. P. Lovecraft, horror fiction, weird fiction, ecocriticism, chronotope